Anthropometric indicators and diabetes incidence: results from a national cohort study, Turkey. (20th October 2021) - Emli Alpay, E; Unal, B; Ergor, G; Dinc Horasan, G; Sozmen, K; Ekinci, B; Sakarya, S
Abstract: Background: Anthropometric indicators such as Body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), waist-to-hip ratio (WHR), and Body Shape Index (ABSI) are used globally to evaluate the risk of type 2 diabetes (T2DM). Our study aimed to investigate associations between different anthropometric indicators and the risk of T2DM using data from a national cohort. Methods: The data on anthropometric measures and other risk factors of diabetes were obtained from Turkey Chronic Diseases and Risk Factors Survey in 2011 (n = 18, 477). Disease information for the years 2012-2017 of the cohort has been reached through electronic health records and DM was ascertained by standard ICD-10 Codes. Four logistic regression models were generated based on different groups of confounders: unmodifiable risk factors, behavioral risk factors, comorbidities and socioeconomic variables. Categorical BMI, WC, WHR, WHtR, and ABSI values were used and adjusted RRs (95% CIs) of measurements were computed for men and women separately. Results: Median follow-up year (IQR) was 6, 46 (0, 06). Between 2012 and 2017, 540 people were diagnosed with new diabetes. All anthropometric measurements except ABSI were associated with T2DM risk in all models. Among the anthropometric measures, BMI showed the strongest effect on incident diabetes, both in men (BMI ≥30; RRadj: 3.06, 95% CI 1.93-4.86) and women (BMI ≥30; RRadj: 2.58; 95%CI 1.73-3.85) in model 4 (adjusting for all confounding factors). WHtR provided the second strongest association with a RRadj of 2.57 in men (95% CI 1.78-3.71) and 2.55 in women (95%CI 1.87-3.47). Conclusions: Independent of other risk factors, individuals with high BMI, WHR, WHtR and WC are at higher risk of developing T2DM. Public health strategies aimed at prevention of weight gain and obesity will probably be the most effective way to struggle with diabetes. Key messages: There is a strong association between anthropometric measurements and type 2 diabetes incidence. Anthropometric indicators can be used to predict the risk of type 2 diabetes in males and females by clinicians and public health practitioners.